Associations between opioid and nicotine dependence in nationally representative samples of United States adult daily smokers. (1st May 2018) - Parker, Maria A.; Streck, Joanna M.; Sigmon, Stacey C.
Highlights: Cessation outcomes among opioid-dependent smokers are 25% that of other smokers. We examined nicotine dependence severity in smokers with and without opioid dependence (OD). Opioid dependence was associated with increased nicotine dependence severity. Findings support efforts to develop more intensive interventions in OD smokers. Abstract: Introduction: Smoking prevalence among adults with opioid dependence far exceeds that of the general population, and cessation outcomes in this group are one-fourth that of smokers without a substance use disorder. Understanding the reasons underlying these poor outcomes is critical for developing more effective smoking interventions in this group. Elevated baseline severity of nicotine dependence is associated with lower rates of smoking cessation over time. We examined whether nicotine dependence severity among smokers may vary as a function of opioid dependence status using nationally representative samples of adult smokers. Methods: Data were derived from multiple years of the National Survey on Drug Use and Health (NSDUH, 2006–2014; n = 58, 971). Nicotine dependence was measured by the Nicotine Dependence Syndrome Scale (NDSS) and the first item (i.e., time to first cigarette) of the Fagerström Test for Nicotine Dependence (FTND). Opioid dependence was assessed using the Diagnostic and Statistical Manual of Mental Disorders criteria. Results: Opioid-dependent smokers exhibited greater severity of nicotine dependence compared to non-opioid dependent smokers, as evidenced by higher mean NDSS scores (p < 0.05). On both NDSS and FTND measures of nicotine dependence, opioid-dependent smokers were also approximately twice as likely to be dependent on nicotine than those not dependent on opioids (p's < 0.05). Conclusions: Opioid dependence is associated with increased severity and prevalence of nicotine dependence among smokers. Considering the disproportionate societal and economic burdens of smoking and smoking-related consequences in this vulnerable population, continued investigations are needed to better understand opioid-dependent individuals' poor cessation outcomes.